Draft Annual Plan 1993-94 Andhra Pradesh Volume-II (Sectoral Programmes) 7. Social Services - Planning Commission (Planning Commission, 1992)
The Directorate of School Education deals with general education at element an and secondary levels and teacher’s education. Budget allotted for this Directorate includes grants to school organisations engaged in the field of education.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh